Assessing fraction knowledge by a digital game. (May 2017) - Ninaus, Manuel; Kiili, Kristian; McMullen, Jake; Moeller, Korbinian
Abstract: Serious or educational games gain increasing research interest as tools to augment traditional instructional approaches on scholastic learning, especially in mathematics education. In this study, we investigated whether game-based approaches may not only be useful to foster numerical learning but may also be valid as an assessment tool. To measure their conceptual knowledge of fractions eleven-year-old students played a math game on tablet computers using tilt-control to navigate an avatar along a number line for a total of 30 min. Findings indicated that hallmark effects of fraction magnitude processing typically observed in basic research, such as the numerical distance effect, were successfully replicated using the game-based assessment. Moreover, fraction comparison performance as well as fraction estimation accuracy correlated significantly with students' math grades. Therefore, the results of the current study suggest that game-based learning environments for fraction education (even using tilt-control) may also allow for a valid assessment of students' fraction knowledge. Highlights: Fraction understanding is an important predictor of mathematics achievement. We used a digital game with tilt control to assess conceptual fraction knowledge. The digital game employed fraction magnitude estimation and comparison tasks. Hallmark effects of fraction magnitude processing were replicated using the game. Additionally, game performance correlated with students' math grades.